2008
DOI: 10.1109/tmi.2007.907323
|View full text |Cite
|
Sign up to set email alerts
|

A Technique for Regional Analysis of Femorotibial Cartilage Thickness Based on Quantitative Magnetic Resonance Imaging

Abstract: The objective of this work was to develop a methodology for measuring cartilage thickness in anatomically based subregions in the tibial and in the central weight-bearing femoral cartilage from magnetic resonance (MR) images. The tibial plateau was divided into a central area of the total subchondral bone area (tAB), and anterior, posterior, internal, and external subregions surrounding it. In the weight-bearing femoral condyles, central, internal, and external subregions were determined. The Euclidean distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
243
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(250 citation statements)
references
References 27 publications
5
243
0
Order By: Relevance
“…1). Several regions of interest have been proposed for mean thickness measurements [4,5,[7][8][9], and the method can be adapted to characterize the thickness shape in these regions rather than in the regions of thicker cartilage, as done in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Several regions of interest have been proposed for mean thickness measurements [4,5,[7][8][9], and the method can be adapted to characterize the thickness shape in these regions rather than in the regions of thicker cartilage, as done in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For a long time, the best measure of cartilage thickness was the tibiofemoral joint space width derived from a knee radiograph. However, this technique is two-dimensional and does not allow for a direct visualization of the cartilage and fine-grained analyses of cartilage thickness [4]. More recently, magnetic resonance imaging (MRI) has replaced radiography, notably because it can visualize articular cartilage with high resolution and is noninvasive [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All morphologic measures mentioned previously were computed, and change (between baseline and follow-up) was measured in the four femorotibial cartilage plates. In order to determine the mean cartilage thickness (ThCtAB.Me and ThCcAB.Me), the mean of two distance transformations, one from the tAB to the AC and one from the AC to the tAB, was considered (28).…”
Section: Methodsmentioning
confidence: 99%
“…Most quantitative studies divide the cartilage into a few compartments and report cartilage thickness (mean and standard deviation) for each compartment. Wirth et al reported a technique for regional analysis of femorotibial cartilage thickness based on quantitative MRI (Wirth et al, 2008). The latter paper uses an elegant algorithm driven identification of sub-regions with user-controlled parameters to define the sub-regions.…”
Section: Introductionmentioning
confidence: 99%